Humanitarian aid storage: way of quick response for victim’s ease before and after the disaster - Jasmani, Ismail; Abdul Rahman, Julaila; Abdul Rani, Abdul Hakim (IIUM Press, 2016)

(untitled)
Global warming nowadays is becoming more hostile as it is a catalyst for the disaster towards the population. The worrying part is the aftermath of the disaster, with a large number of victims suffered lack of food resources and shelter. Although the government and non-government organization (NGOs) are distributing the resources especially food rations, they have the problems such as inefficient distribution of the ration to the victims’ area, transportation and packaging design. The affected areas sometimes cannot be reached due to poor transportation, lack of manpower and poor storage or packaging of humanitarian aid. Therefore, this research proposes the humanitarian aid storage condition that consider the period of time and effect towards the physical properties. The humanitarian aid will consist of basic supplies and resources such as food, medicine and other items for daily use that can last for 3 days after the disaster. The humanitarian aid storage will have to be practical, with its period of time and effect to the ration taken into consideration such as the durability, stiffness, its possible duration of usage need to be tested through its physical properties. Interview, questionnaire and observation will be done to get detailed information. The respondents will be from different age groups as well as several areas so that more accurate data will be collected especially on ways to distribute and handling the storage. Targeted respondents are between 35 to 50 victims in respective areas. The site visit will be done at Kampong Seberang, Kampong Telok Ira and others area at Temerloh, Pahang Darul Makmor. To study the storage period of time and effect towards the physical properties, several tests should be made. Through this observation, the storage condition and period of time will influence and affect the physical properties of humanitarian aid goods to ensure it is suitable for the comfort and usefulness to the victims.